Mutual neutralisation of O+ with O−: investigation of the role of metastable ions in a combined experimental and theoretical study. Issue 43 (2nd November 2021) - Poline, Mathias; Dochain, Arnaud; Rosén, Stefan; Grumer, Jon; Ji, MingChao; Eklund, Gustav; Simonsson, Ansgar; Reinhed, Peter; Blom, Mikael; Shuman, Nicholas S.; Ard, Shaun G.; Viggiano, Albert A.; et al.
Abstract : The mutual neutralisation of O + with O − has been studied in a double ion-beam storage ring with combined merged-beams, imaging and timing techniques. Abstract : The mutual neutralisation of O + with O − has been studied in a double ion-beam storage ring with combined merged-beams, imaging and timing techniques. Branching ratios were measured at the collision energies of 55, 75 and 170 (± 15) meV, and found to be in good agreement with previous single-pass merged-beams experimental results at 7 meV collision energy. Several previously unidentified spectral features were found to correspond to mutual neutralisation channels of the first metastable state of the cation (O + ( 2 D o ), τ ≈ 3.6 hours), while no contributions from the second metastable state (O + ( 2 P o ), τ ≈ 5 seconds) were observed. Theoretical calculations were performed using the multi-channel Landau–Zener model combined with the anion centered asymptotic method, and gave good agreement with several experimentally observed channels, but could not describe well observed contributions from the O + ( 2 D o ) metastable state as well as channels involving the O(3s 5 S o ) state.